Ceramic contexts of the occidental necropolis in Troia (Portugal) - Vaz Pinto, Inês; Magalhães, Ana Patrícia; Araújo dos Santos, Filipa; Figueiredo, Margarida; Miranda, Andreia (Rei Cretariae Romanae Fautorum Acta, 2024)
The recent excavation of an area lying northwest of the so-called Mensa-Tomb Necropolis (excavated in the 1970s) at the site of Troia revealed the continuation of the same funerary area, the whole cemetery having been recently renamed as Occidental Necropolis. Similar rectangular and sigma-shaped mensa tombs were exposed, but heavy disturbance caused by several interventions in the relatively recent past also revealed earlier phases of the necropolis. Relative stratigraphy and tomb type allowed the grouping of some 60 tombs into four main phases. The ceramics collected in the recent excavation of the necropolis (2021), and especially the sigillata and the amphorae, indicate funerary activity running from the 2nd century until the second half of the 4th century AD.